Magnetostriction of Sm-Fe and Sm-Fe-B thin films fabricated by RF magnetron sputtering - Lim, SH; Choi, YS; Han, SH; Kim, HJ; Shima, T; Fujimori, H (ELSEVIER SCIENCE BV, 1998)
Magnetostriction of amorphous Sm-Fe and Sm-Fe-B thin films is systematically investigated over a wide composition range from 14.1 to 71.7 at% Sm. In the case of Sm-Fe-B thin films, the amount of B is varied from 0.3 to 0.8 at%. Good magnetostrictive characteristics, particularly at low magnetic fields, are achieved in both Sm-Fe and Sm-Fe-B thin films, although better properties are observed in B containing Sm-Fe thin films. At a magnetic field of 100 Oe, for example, the magnitude of magnetostriction is - 350 ppm in a Sm-Fe thin film and it is - 470 ppm in a B containing Sm-Fe thin film. With their excellent magnetostrictive characteristics, the present Sm-Fe and Sm-Fe-B thin films are considered to be suitable for Si based microdevices. (C) 1998 Published by Elsevier Science B.V. All rights reserved.
Keywords: GIANT MAGNETOSTRICTION; ANISOTROPY; ALLOYS